A relevance model for middle school students seeking information for an inquiry-based class history project. Issue 2 (March 2017) - Cole, Charles; Beheshti, Jamshid; Abuhimed, Dhary
Highlights: Field study of 60 middle school students researching their class history project Relevance criteria achieved through students constructing topic frame Findings show 3-phase relevance process 2/3 of study participants did not achieve Verticalizing 3rd phase Relevance model proposed that indicates path for facilitating Verticalizing 3rd phase Abstract: The article reports a field study of 60 grade-eight students seeking information for their 4-month long, thesis-based class history project. The study asked: What is relevance for the group studied, and how does relevance evolve over the course of the students' 4-month history project? Instead of investigating a unitary concept of relevance, our conceptual framework considers both topical and psychological relevance as defined by Harter (1992). The 60 student participants were divided into three groups based on their instructors' marks. We then utilized the constant comparative method of Glaser and Strauss's grounded theory approach to code 2 class assignments that formed part of the history project. Study findings indicate that psychological relevance is constructed by the students in Associating, Translating and Verticalizing phases. Topical relevance only occurs in the Verticalizing third phase. Students in the High Mark Group indicated significantly higher instances of the Verticalizing phase than the Low and Middle Mark Groups who were stuck in the Associating and Translating phases. Students can be aided in this difficult process of constructing an effective relevance criteria framework via the design of personalized information systems that facilitate students' involvement of their prior knowledge and belief systems in the relevance assessment process.